Digit and Ungual Morphology Suggest Adaptations for Scansoriality in the Late Carboniferous Eureptile Anthracodromeus longipes - Mann, Arjan; Dudgeon, Thomas W.; Henrici, Amy C.; Berman, David S; Pierce, Stephanie E. (Frontiers in Earth Science, 2021)
A new skeleton of the exceedingly rare, late Carboniferous eureptile Anthracodromeus longipes Carroll and Baird, 1972, reveals the presence of a reduced phalangeal count in the manus and pedes and uniquely recurved claws. With these data, we quantitatively evaluate the locomotor ecology of Anthracodromeus using morphometric analyses of the phalangeal proportions, claw curvature, and claw shape. Our findings indicate that the anatomy of Anthracodromeus likely facilitated scansorial clinging to some degree via recurved claws and increased surface area of the large manus and pes. This suggests that Anthracodromeus was among the earliest amniotes to show climbing abilities, pushing back the origins of scansoriality by at least 17 million years. It further suggests that scansoriality arose soon after the origin of amniotes, allowing them to exploit a wide range of novel terrestrial niches.